Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1525-1438.2006.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism syndrome in gynecological cancer

Abstract: Venous thromboembolism (VTE) could be presented as an initial clinical feature in some cancer patients or a complication followed by various cancer treatments, which all indicates a poor outcome. This review focuses on elucidating the relationship of VTE and the main gynecological cancers including ovarian, endometrial, and cervical cancers. First, the general VTE information about gynecological cancer are introduced; second, the risk factors of VTE developing in gynecological cancer were discussed; third, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 130 publications
1
6
0
Order By: Relevance
“…In this study we observed approximately a two-fold increase in the level of cadmium in blood of the smokers in all the examined groups over the non-smokers. However, the mean BCd IJOMEH 2013;26(2) 298 parameter that can gauge ongoing fibrin formation and degradation in some diseases, including ovarian cancer [29,45]. In our research, like in von Tempelhoff et al study [19] we have shown a two-fold increase of fibrin D-dimer plasma level, which correlated with fibrinogen level, in the women with endometrial cancer as compared to the control group.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In this study we observed approximately a two-fold increase in the level of cadmium in blood of the smokers in all the examined groups over the non-smokers. However, the mean BCd IJOMEH 2013;26(2) 298 parameter that can gauge ongoing fibrin formation and degradation in some diseases, including ovarian cancer [29,45]. In our research, like in von Tempelhoff et al study [19] we have shown a two-fold increase of fibrin D-dimer plasma level, which correlated with fibrinogen level, in the women with endometrial cancer as compared to the control group.…”
Section: Discussionsupporting
confidence: 67%
“…This may suggest that cadmium exerts toxic effect on the vascular endothelium leading to hypercoagulability. However, it has been observed that coagulation factors and regulatory proteins are upregulated in the patients with gastric cancer [27], colorectal cancer [28], gynecological cancer [29], and cervical cancer [30]. However, there are no studies on women with myoma, except for some data in literature from the 1960s [31].…”
Section: Discussionmentioning
confidence: 99%
“…Many variables regarding advanced disease were identified as significant risk factors for VTE before treatment Thromboembolism in endometrial carcinoma T Satoh et al in endometrial cancer, whereas our recent study revealed that various risk factors regarding advanced disease other than massive ascites were not significant risk factors for VTE before treatment in ovarian cancer. As for VTE after surgery or during treatment, a considerable number of previous reports have indicated advanced disease as a significant risk factor for VTE in gynaecological malignancies (Dubuc-Lissoir et al, 1999;Agnelli et al, 2006;Wang et al, 2006). Among non-endometrioid histologies, clear cell histology seems to represent the highest risk factor (clear cell histology, 4 out of 6 (66.7%); non-clear cell histology, 4 out of 15 (26.7%)).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient population included women with ovarian, uterine, and cervical malignancies; the majority of patients were treated for ovarian cancer, a patient group that is associated with a higher incidence of VTE than other gynecologic malignances 21. There were no findings of PE or DVT in follow-up, and there were few filter-related complications.…”
Section: Discussionmentioning
confidence: 99%